Ownership Ambiguity: A Study of Compensation for Crop Damage in Coconut Pawn Transactions in Islamic and Customary Law - Farida Arianti; Silvianetri Silvianetri; Akmal Bashori; Iza Hanifuddin; Abdul Mughits; Maisarah Leli (Khazanah Hukum, 2025)
Control of the pawned coconut object over the damaged plants around the pawned object. The pawnbroker demands compensation for the damage to his plants around the pawned coconut tree. The purpose of this study is to examine how the control of the parties who carry out plant pawn transactions is exercised and how the legal responsibility is when damage occurs to the plants around the collateral object. This type of research is in the form of field research in the Lima Kaum Batusangkar area of ​​Indonesia. This study is descriptive qualitative with a case study approach. Primary sources from both parties who carry out the coconut tree pawn agreement. Secondary sources from the local community. Data collection techniques through in-depth interviews and observations. Analysis techniques with qualitative descriptive analysis. Findings from the field show that the pawnbroker still has power over the land where the coconut grows and plants young plants in the form of cayenne pepper around the area, while the pawn recipient also has power over the coconut fruit that has been pawned to him. This study concludes that compensation for damaged plants cannot be justified according to Custom, because the cayenne pepper plants prevent the pawn recipient from taking the fruit, in line with the pawn recipient's power, which includes the boundaries of the coconut tree land attached to immovable objects (land). According to Islamic jurisprudence, this is a naqish (limited time) property right, only one of which is owned (material or benefit).